Sheehan’s Syndrome with Dilated Cardiomyopathy: An Overlooked Sequela of Postpartum Hemorrhage - Imran, Jabar; Nayyar, Shahroze; Hamid, Jahanzaib; Ashraf, Iqra (Journal of Rawalpindi Medical College, 2026)
We present the case of a 43-year-old female who developed panhypopituitarism as a sequela of postpartum hemorrhage. She manifested with recurrent vomiting, diarrhea, hypotension, and hypoglycemia, and was subsequently diagnosed with Sheehan’s syndrome complicated by dilated cardiomyopathy.Prompt initiation of hormonal replacement therapy resulted in remarkable clinical improvement. This case emphasizes the critical need for early recognition of Sheehan’s syndrome in women with a history of obstetric hemorrhage, particularly when presenting with chronic, nonspecific complaints, to prevent life-threatening complications. Keywords: Sheehan syndrome; postpartum hemorrhage; hypopituitarism; dilated cardiomyopathy; heart failure